Can nut consumption improve colon cancer survival? - Aune, Dagfinn (Translational Gastroenterology and Hepatology, 2018)
Fadelu et al. recently examined the association between nut consumption and survival among patients with stage 3 colon cancer in an article published in the Journal of Clinical Oncology (1). Risk factors of incident colon cancer have been comprehensively examined in many previous studies and both dietary and other lifestyle factors have been associated with colon cancer incidence (2-6).